2023
DOI: 10.3390/axioms12010081
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Mechanical Properties of Rubberized Concrete Incorporating Fly Ash and Nano Silica by Artificial Neural Network Technique

Abstract: The use of enormous amounts of material is required for production. Due to the current emphasis on the environment and sustainability of materials, waste products and by-products, including silica fume and fly ash (FA), are incorporated into concrete as a substitute partially for cement. Additionally, concrete fine aggregate has indeed been largely replaced by waste materials like crumb rubber (CR), thus it reduces the mechanical properties but improved some other properties of the concrete. To decrease the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 56 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…The parameters with relatively lower accuracy in comparison with Fc and Ff are γf and $. Several studies have also reported the suitability of a machine learning approach for the prediction of concrete strength with high accuracy and stability [36,37] Examination of MoD values gives sufficient information about the error rates of the ANN model. However, in order to make the prediction error analysis of the ANN model more comprehensive, it is important to examine the target values for each data point and the prediction values obtained from the ANN model.…”
Section: Ann Modelmentioning
confidence: 99%
“…The parameters with relatively lower accuracy in comparison with Fc and Ff are γf and $. Several studies have also reported the suitability of a machine learning approach for the prediction of concrete strength with high accuracy and stability [36,37] Examination of MoD values gives sufficient information about the error rates of the ANN model. However, in order to make the prediction error analysis of the ANN model more comprehensive, it is important to examine the target values for each data point and the prediction values obtained from the ANN model.…”
Section: Ann Modelmentioning
confidence: 99%
“…ANNs are also actively used to predict various properties of concrete made using various modifying additives, fiber fibers, lightweight and recycled aggregates, and the developed models show fairly accurate results [36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Through years of experiments and research, ANN techniques have demonstrated robust learning capabilities and high prediction accuracy through its ability to identify complex mathematical relationships between input and output variables [ 20 ]. Accordingly, ANN models have been widely used in the literature as predictive techniques in a range of different fields, including healthcare [ 21 , 22 ], sustainable development [ 18 , 19 , 23 ], agriculture [ 23 , 24 ], and material science [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%